La arquitectura jesuítico-guaraní : una experiencia de interacción cultural - Levinton, Norberto; Carbonell de Masy, Rafael (Buenos Aires : Editorial SB, 2008)
Ethnological and anthropological studies of the architecture of the 17th century Jesuit guarani missions in Argentina, in what the author considers archaeological evidence of the integration of the European and Guaran structural concepts of space and typology in the construction of the missions. The study of the ruins located in the province of Misiones in the northeastern region of Argentina confirm how the use of colonial science left, amongst other practices the participation and professionalization of the guaran Indians in the skilled activities of the colonial society, including the construction of buildings.
Incluye referencias bibliográficas.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2023. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Jesuitas -- Misiones -- América del Sur; Arquitectura -- América Latina; Indios de Sudamérica -- Misiones; Arquitectura jesuítica -- América del Sur; Edificios de la misión española -- América del Sur; Arquitectura y sociedad -- América del Sur; Libros electrónicos.